Diversifying selection is the dominant factor affecting the geographical variation of MHC class II genes in the Omei tree frog. (14th August 2016) - Li, J.; Shen, H.; Wang, H.; Zhao, M.; Luo, Z.; Wu, H.
Abstract: Genes encoding the major histocompatibility complex (MHC) are excellent candidates for elucidating adaptive variation because of their essential role in immune function. Hypotheses for how genetic variations of MHC genes are maintained include balancing selection, diversifying selection and neutral events; however, which of these forces are dominant remains controversial. In this study, we determined the preliminary forces that shaped MHC geographical variation in Omei tree frog by comparing with neutral microsatellites. The results revealed high genetic diversity and significant population differentiation in MHC genes of this species. The differentiation patterns of MHC and microsatellites were uncorrelated. Stronger level of genetic differentiation in MHC genes compared with that in microsatellites (based on comparison in both genetic differentiation patterns and strength of isolation by distance patterns) indicates the effects of diversifying selection on the geographical variation of MHC genes. Considering the significant evidence of positive selection acting on antigen‐binding sites, we presumed that selection pressures may be mainly from locally different pathogens when gene flow is restricted. The results of this study contribute to a more comprehensive understanding of the evolutionary forces that maintain MHC geographical variation among natural populations. Abstract : This study determined the preliminary forces shaping MHC geographical variation in Omei tree frog (Rhacophorus omeimontis) by comparing them with neutral microsatellites. The results revealed high genetic diversity and significant population differentiation in MHC genes of this species. Stronger level of genetic differentiation in MHC genes compared with that in microsatellites indicates the effects of diversifying selection on the MHC geographical variations. Considering the significant evidence of positive selection acting on antigen‐binding sites, we presumed that selection pressures may be mainly from local pathogens when gene flow is restricted. This information contributes to a more comprehensive understanding of the evolutionary forces that maintain MHC geographical variation among natural populations.